Datenschutz Minderjähriger Geschäftsfähigkeit als Grundlage der Einwilligungsfähigkeit im Datenrecht - Schrader, Julius (Mohr Siebeck, 2021)
Minors come into contact with data-intensive applications such as social media networks online. Julius Schrader discusses at what age and under which conditions minors can effectively consent to data processing and conclude relevant contracts. In light of the General Data Protection Regulation and German national law, he proposes a comprehensive regulation to protect minors
PublicationDate: 20211004
Keywords: Social Media -- Unternehmerisches Ermessen -- Art. 8 Datenschutzgrundverordnung -- Vertrag Dienst gegen Daten -- Widerruf der datenschutzrechtlichen Einwilligung -- Masoretischer Text -- Kopplungsverbot, Art. 7 Abs. 4 DS-GVO -- Zivilgesetz -- Bürgerliches Recht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung